Tsunami Susceptibility Assessment Using Spatial Multi-Criteria Evaluation in Watukarung, Pacitan - Ikhwan Amri; Bella Sinta Hikmasari; Cornelius Antoni Nababan; Dessy Ayu Wijayanti; Dina Ruslanjari; Sri Rum Giyarsih (Universitas Negeri Medan, 2023)
Tsunamis are natural hazards that have the potential to cause significant damage and losses to the South Coast of Java. As the initial foundation for local spatial planning and risk reduction, preparing a tsunami susceptibility mapping is imperative to minimize the disaster's impact. This study aims to identify the spatial distribution of tsunami susceptibility in Watukarung Village, Pacitan Regency, using the Spatial Multi-Criteria Evaluation (SMCE) method. The variables involved in the modeling include landform, elevation, slope, distance from the shoreline, and distance from the river. The value and weight of each factor were determined using the pairwise technique in the SMCE framework. The research results indicated that the tsunami susceptibility in Watukarung comprises four classes: safe (598.40 ha), low (9.68 ha), moderate (23.92 ha), and high (25.13 ha). The areas most prone to tsunamis are generally identified in the southern part of Watukarung, which is generally associated with beach or alluvial plain landforms, very close to shore, and low land elevation. Ironically, human settlements and coastal tourism are overgrowing in the tsunami-prone zone, highlighting that risk reduction measures must be implemented optimally to anticipate tsunami hazards. As a recommendation, further research must be carried out to comprehensively represent the tsunami risk in the Watukarung coastal region. Keyword: Tsunami, Susceptibility, Spatial Multi-Criteria Evaluation, Watukarung, Pacitan